TESTING OF INDIVIDUAL SENSITIVITY TO RADON AND THORON EXPOSURE BY IN VITRO IRRADIATION OF LYMPHOCYTES CULTURE - CIORBA, Daniela; FODOR, Eva; COSMA, †Constantin; ALBERT-ANI, Doina; MOLDOVAN, Mircea (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
Identify the factors that affect individual sensitivity is a very important step in cancer risk assessment at low doses or low doses rates, according with study of dose-response relationship. DNA damage response processes are likely to play an important role in radiation by cancer risk association. This paper tries to quantify the individual sensitivity to alpha particles exposure using an in vitro exposure model. Quantify of DNA lesions by comet assay, in lymphocytes cultures exposed to the same doses of radiation was made. The irradiation was performed using the pitchblende ore during a 72 hours period, intermittent exposure with dose rates of 89.15 kBq/m3. The lowest and highest Radon Thoron concentrations computed in this study were 89.15 kBq/m3 and 212.9 kBq/m3, respectively. The study was done for healthy donors, comparatively with chronic obstructive pulmonary diseases donors. Ageing in vitro of lymphocytes cultures exposed to low doses of ionizing radiation is the biological model used, which are presented here. Based on these results, a standard test should be develop and applied for study of sensitivities in average population groups.